Salt-Assisted Mesostructured Cellular Foam (MCF) Silica Synthesis from Bagasse Bottom Ash for Enzymatic Starch Hydrolysis - Agustian, Joni; Hermida, Lilis (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Synthesis of MCF silica is presently conducted solely using TEOS and TMB, with the purpose of immobilizing amylolytic enzymes. Utilizing BBA and KCl to create the salt-assisted MCF silica present a viable option for converting a natural waste into an effective enzyme carrier, given its substantial silica content. The objectives were to produce the MCF silica, to employee the MCF silica as the glucoamylase carrier, and to know characteristics of the immobilized enzyme by conducting hydrolysis of starches. The carrier had surface area of 45.5 m2 g-1, pore volume of 0.12 cm3 g-1, pore size of 9.3 nm, and mesoporous silica type IV. Reduction in the carrier pore diameter and the medium to strong FTIR vibrations indicated free glucoamylase immobilization on carrier. The immobilization reached 88.5% efficiency, influenced by factors such as initial enzyme concentration, PO₄ buffer pH, and temperature, with agitation speed having a minor impact. This optimum value was obtained at the initial enzyme concentration of 9.0 mg mL-1, agitation speed of 120 rpm, buffer pH of 5.5, and temperature of 30°C. Hydrolysis of starches (tapioca, wheat, potato, corn) resulted in Dextrose Equivalent (DE) values ranging from 5.1% to 63.9%, with the immobilized glucoamylase showing better performance in potato starch hydrolysis (DE of 63.9%) and corn starch (DE of 45.6%). The use of BBA in synthesis of the salt-assisted MCF silica proved to be a viable and sustainable alternative for enzyme immobilization, with potential applications in industrial starch hydrolysis.